Deep vein thrombosis prophylaxis in patients who undergo knee arthroscopy: a systematic review - Udit Dave; Emma G. Lewis; Victoria K. Ierulli; Shreya M. Saraf; Mary K. Mulcahey (Knee Surgery & Related Research)
Abstract Background Knee arthroscopy is one of the most common procedures performed by orthopedic surgeons. A potentially life-threatening complication following this procedure is deep vein thrombosis (DVT). DVT prophylaxis can be obtained both mechanically (e.g., compression stockings) and chemically (e.g., aspirin, anticoagulants, and factor Xa inhibitors). Currently, there is no standardized guideline for DVT prophylaxis following knee arthroscopy. The purpose of this systematic review was to summarize how DVT prophylaxis is employed for patients who undergo knee arthroscopy. Methods PubMed, Embase, and Cochrane Library were searched for studies published after 1998 according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies were included if they evaluated DVT prophylaxis regimens in patients of any age who underwent knee arthroscopy. Studies not written in English, that analyzed animals or cadavers, that did not directly evaluate patients undergoing knee arthroscopy, or that did not address DVT prophylaxis were excluded. Results The initial search identified 300 studies, 15 of which were included. These 15 studies examined methods of DVT prophylaxis, including compression stockings (2 of 18; 11%), aspirin (1 of 18; 6%), factor Xa inhibitors (2 of 18; 11%), low-molecular-weight heparin (12 of 18; 67%), and neuromuscular electrical stimulation (1 of 18; 6%). Overall, 7 of 15 (47%) studies recommended DVT prophylaxis in all patients, and 3 (20%) studies supported its use for high-risk patients. Five (33%) studies did not support DVT prophylaxis, citing low incidence of postoperative DVT. Conclusions Compression stockings, aspirin, factor Xa inhibitors, and low-molecular-weight heparin (LMWH) were identified as possible options for DVT prophylaxis in patients undergoing knee arthroscopy. For high-risk knee arthroscopy patients, factor Xa inhibitors and LMWH drugs are appropriate for DVT prophylaxis. Level of evidence Level III, systematic review of level I–III studies.